A catalogue of the types of Limoniidae and Tipulidae (Diptera: Tipulomorpha) in the collection of the Museu de Zoologia da Universidade de São Paulo, Brazil - Ribeiro, Guilherme Cunha; Lamas, Carlos José Einicker; de Azevedo, Leisa Nathalie Silva (Zootaxa, 2007)
Following a recommendation of the International Code of Zoological Nomenclature, a catalogue of the type-specimens of Tipulomorpha (Diptera) held in the collection of the Museu de Zoologia da Universidade de São Paulo, state of São Paulo, Brazil (MZSP), is provided, with information on 118 types (including 72 primary types) of 89 Neotropical (mostly Brazilian) taxa of the families Limoniidae and Tipulidae.